Pengaruh Pemberian Susu Kedelai Terhadap Tingkat Tekanan Darah Pada Wanita Perimenopause Di Desa Ensalang Tahun 2022 - Hearty Efifania Ose Payon; Silvia Finida Hannisa; Asri Fitri Yati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Perimenopause is a transitional phase between premenopause and postmenopause. This phase is characterized by an irregular menstrual cycle with prolonged heavy menstrual bleeding and relatively large amounts of menstrual blood, sometimes accompanied by menstrual pain (dysmenorrhea). In certain women, vasomotor complaints and complaints of premenstrual syndrome have arisen (Baziat, Ali. 2020). The most common complaints include vasomotor symptoms such as hot flushes, night sweats, insomnia, fatigue and palpitations.